Cyfrowe nadzieje edukacyjne, rozczarowania, realia: ani fanfary, ani elegie - Goban-Klas, Tomasz (Wydawnictwo Naukowe UAM, 2012)
Education is an extremely complex task. An admiration of technology gadgets does not help, history gives us many examples of the great hopes for the introduction of new media, then they ended in great disappointment. However, digital school is neither utopia nor dystopia, it is the future of education, which as in the past has never been perfect, but it was necessary. Digital reconstruction of education requires the participation of teachers, and not – as so far – the politicians throwing slogans and a bit of money on equipment that will soon become cheaper, and certainly outdated. This requires teaching educators, the preparation of “digital” multimedia programs and textbooks, assignments, and many other activities. And support by the achievements of foreign and Polish pedagogy, including works by renowned Poznań school on didactic technology.
Digital educational hopes, disappointments, reality: no fanfares, no elegies